In Vitro Susceptibility Studies with Cefaclor and Cephalexin - Scheld, W. Michael (1977)
The in vitro activity of cefaclor and cephalexin against clinical isolates of four bacterial genera was compared. Both agents had a similar range of activity, but cefaclor was significantly more active by weight than cephalexin for most isolates tested.